2015
DOI: 10.1007/s10551-015-2625-1
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analytic Review of Ethical Leadership Outcomes and Moderators

Abstract: A growing body of research suggests that follower perceptions of ethical leadership are associated with beneficial follower outcomes. However, some empirical researchers have found contradictory results. In this study, we use social learning and social exchange theories to test the relationship between ethical leadership and follower work outcomes. Our results suggest that ethical leadership is related positively to numerous follower outcomes such as perceptions of leader interactional fairness and follower et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

33
443
1
28

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 473 publications
(505 citation statements)
references
References 105 publications
33
443
1
28
Order By: Relevance
“…Individuals who have been exposed to a moral entrepreneur are more likely to become a moral entrepreneur themselves because they have experienced its potential and attraction and how it is done. The positive outcomes of ethical leadership that Bedi et al (2016) observed (such as job satisfaction, commitment, organizational citizenship behavior, job performance, job engagement, and organizational identification), together with the negative outcomes (such as turnover intentions, counterproductive work behavior, and relationship conflict) could also apply, whether stronger or weaker, to moral entrepreneurship. This is because followers of moral entrepreneurs are likely to feel more stimulated and inspired, which improves their behavior and well-being.…”
Section: A Model Of Moral Entrepreneurshipmentioning
confidence: 99%
See 4 more Smart Citations
“…Individuals who have been exposed to a moral entrepreneur are more likely to become a moral entrepreneur themselves because they have experienced its potential and attraction and how it is done. The positive outcomes of ethical leadership that Bedi et al (2016) observed (such as job satisfaction, commitment, organizational citizenship behavior, job performance, job engagement, and organizational identification), together with the negative outcomes (such as turnover intentions, counterproductive work behavior, and relationship conflict) could also apply, whether stronger or weaker, to moral entrepreneurship. This is because followers of moral entrepreneurs are likely to feel more stimulated and inspired, which improves their behavior and well-being.…”
Section: A Model Of Moral Entrepreneurshipmentioning
confidence: 99%
“…This context is marked by two crises: the dot-com crisis involving several accountancy frauds at the start of this century, and the financial-economic crisis that started toward the end of the first decade of this century. Many publications on ethical leadership, such as Treviño et al (2003), Brown et al (2005), Treviño (2006, 2014), Schaubroeck (2009), Kalshoven et al (2011b), Eisenbeiß and Giessner (2012), Yukl et al (2013), and Bedi et al (2016), start with references to the business scandals and hold these up as a reason for studying and improving ethical leadership. These scandals illustrate that prevailing norms were violated.…”
Section: The Moral Entrepreneurmentioning
confidence: 99%
See 3 more Smart Citations